Toll-like receptor 4 pathway evolutionary trajectory and functional emergence - Verma, Shailya; Sowdhamini, Ramanathan (Frontiers in Immunology, 2025)
IntroductionToll-like receptors 4 (TLR4) recognize lipopolysaccharides (LPS) from bacteria as their conventional ligands and undergo downstream signaling to produce cytokines. They mediate the signaling either by the TIRAP-MyD88 complex or by the TRAM-TRIF complex. The MyD88 pathway is common to all other TLRs, whereas the TRAM-TRIF complex is largely exclusive to TLR4. Here we study the TIR domain of TRAM and TRIF ortholog proteins that are crucial for downstream signaling. Our previous work on pan-genome-wide survey, indicates Callorhincus milli to be the ancestral organism with both TRAM and TRIF proteins.MethodsTo gain a deeper insight into the protein function and to compare them with Homo sapiens adaptor proteins, we modeled the docking of the TRAM–TRIF complex of representative organisms across various taxa. These modeling experiments provide insights to ascertain a possible interaction surface and calculate the energetics and electrostatic potential of the complex. Furthermore, this enables us to employ normal mode analysis (NMA) to examine fluctuating, interacting, and other specific residue clusters that could have a role in protein functioning in both C. milli and H. sapiens. We also performed molecular dynamics simulations of these complexes and cross-validated the functionally important residues using network parameters.ResultsWe compared the stoichiometry of TRAM–TRIF complexes and found that the tetrameric models (TRAM and TRIF dimer) were more stable than the trimeric model (TRAM dimer and TRIF monomer). While the critical residues of TIRAP, TRIF, and MyD88 were preserved, we also found that the important residues of TRAM signaling were not conserved in C. milli.DiscussionThis suggests the presence of functional TIRAP–MyD88-mediated TLR4 signaling and TRIF-mediated TLR3 signaling in the ancestral species. The overall biological function of this signaling domain appears to be gradually acquired through the orchestration of several motifs through an evolutionary scale.